Strategi Komunikasi Pemasaran Terpadu dalam Peningkatan Jumlah Nasabah Tabungan E’BATARAPOS pada Bank Tabungan Negara (BTN) Kantor Cabang Cibinong - Jayanti, Putri; Maulina, Anita (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
The purpose of this study is to find out how the marketing communication strategy of Bank Tabungan Negara Cibinong Branch Office in increasing the number of e’BATARAPOS customers. The study method used is qualitative. Data collection techniques in this study are interviews, documentation and observation. The results of this study show that Bank Tabungan Negara Cibinong Branch Office has not implemented a marketing communication strategy optimally due to several obstacles including there are no employees who hold the position of Branch Service & Alliance Sales (BSAS), Inadequate Information Technology System and the conditions of the covid 19 pandemic. This is evidenced by the decline in the number of e’BATARAPOS customers in 2020. Bank Tabungan Negara Cibinong Branch Office must immediately fill the vacancy in the BSAS position, improve the information technology system and maximize social media or other digital platforms so that information and promotions of e’BATARAPOS savings are remain conveyed to the public.